Immunohistochemical evaluation of p53 expression in lung cancer of patients with paraneoplastic rheumatic syndrome - Lysenko, S.A. (Experimental Oncology, 2013)
Aim: To study p53 expression in the tumor tissue of lung cancer (LC) patients with paraneoplastic rheumatic syndrome (PNRS). Materials and Methods: There have been used either biopsy or surgically resected tumor samples of 140 LC patients (83 patients without PNRS, 57 patients with PNRS). For evaluation of p53 expression in LC samples, immunohistochemical analysis was performed. Results: It has been shown that p53 expression in tumor samples from LC patients with PNRS was significantly higher compared to that in LC patients without PNRS. It has been shown that p53 expression is more frequently registered in patients with lung adenocarcinoma with PNRS than in patients with lung adenocarcinoma without this syndrome. Conclusion: The presence of PNRS in LC patients with p53 expression is associated with higher aggressiveness of tumor.